Green book [videorecording (DVD)] - Farrelly, Peter; Mortensen, Viggo, 1958-; Ali, Mahershala, 1974-; Cardellini, Linda, 1975- (Universal Pictures Home Entertainment, 2019)
When Tony Lip, a bouncer from an Italian-American neighborhood in the Bronx, is hired to drive Dr. Don Shirley, a world-class Black pianist, on a concert tour from Manhattan to the Deep South, they must rely on The Green Book to guide them to the few establishments that were then safe for African-Americans. Confronted with racism, danger, as well as unexpected humanity and humor, they are forced to set aside differences to survive and thrive on the journey of a lifetime. Inspired by a true friendship.